Traductor de señalización SIP a CAMEL para la tarificación de abonados en una plataforma Online Charging System (OCS) - Cerna Belleza, Jimmy Paul (2015)
This project aims to develop a model of underwriter voice call rate for subscribers CONTROL (limited subscriber monthly consumption in seconds) of the fixed telephone network for management and billing of their calls carried on the platform Charging Only System (OCS), the model is based on the implementation of three important points are: the Translation of SIP / CAMEL / SIP communication between the fixed network and the OCS platform, the decoder of Call Detail Record (CDR) and provisioning and / or subscribers plan creation. The SIP signaling translator SIP / CAMEL receives SIP signaling messages that are generated in the fixed network and its equivalent in CAMEL transmitted through the STP's (signaling transfer point) network for communication with OCS platform which validates if the subscriber has balance to allow the requested call. The encoder of the CDRs generated by the OCS platform to validate that pricing has been generated correctly by the time fields, call destination and fare, also to identify the required fields for the billing process. Stage of supply and / or creation of subscriber plans to create the profile OCS platform that each subscriber should belong or be part of the group of fixed lines in the plans defined rates and destinations will be possible to generate by this group.